Association between HDL Cholesterol Levels and the Consumption of Vitamin A in Metabolically Healthy Obese Lebanese: A Cross-Sectional Study among Adults in Lebanon. (3rd June 2018) - Zalaket, J.; Hanna-Wakim, L.; Matta, J.
Abstract : Objectives. Previous studies show the association between vitamin A and elevation of plasma triglyceride concentrations. However, limited information exists on the association between vitamin A and plasma HDL cholesterol concentrations. The aim of this study is to investigate the association between plasma HDL cholesterol levels and vitamin A intake in 57 metabolically healthy obese (MHO) Lebanese. Methods. Out of the 112 adult obese participants who had completed anthropometric and biochemical data, 57 (22 males and 35 females) aged 18–62 years old are metabolically healthy and their data are included in this study. A valid semiquantitative food frequency questionnaire (SQFFQ) was used to test vitamin A intake among other antioxidants. The participants were recruited from the database of three dietary clinics across Lebanon. Results . Pearson's correlation coefficient was used to measure the strength of the relationship between vitamin A and plasma HDL cholesterol levels. There was a significant positive correlation (P value = 0.0225) between vitamin A consumption and HDL cholesterol serum levels in obese participants; when vitamin A levels decrease, HDL levels decrease more in female than in male participants. Conclusion . The association between dietary vitamin A, a powerful antioxidant, and high HDL levels is shown in MHO but should be further exploited in future studies.